How does ESG rating disagreement influence analyst forecast dispersion? - Robin Spira (Junior Management Science (JUMS), 2024)
The practice of responsible and sustainable investing has led to the incorporation of environmental, social and governance (ESG) information into investment decisions. The role of ESG rating agencies has been to facilitate decision-making by aggregating unstructured ESG information into a single rating. Market participants, such as financial analysts, rely on these ratings as part of their research. However, ESG rating agencies rarely agree in their assessment of a company's ESG performance, leading to divergent ESG ratings. This paper uses an OLS regression model based on a large sample of firm data to investigate whether ESG rating agency disagreement increases analysts' forecast dispersion. It builds on previous research by Kimbrough et al. (2022). The results do not provide sufficient evidence to support a significant relationship between ESG discrepancies and analyst forecast dispersion. This calls into question the importance of non-financial ESG information in analysts' assessment of a company's financial performance.
Keywords: 650; analyst forecast; disagreement; ESG rating agencies; ESG score; intermediaries